Household Air Pollution Concentrations after Liquefied Petroleum Gas Interventions in Rural Peru: Findings from a One-Year Randomized Controlled Trial Followed by a One-Year Pragmatic Crossover Trial - Fandiño-Del-Rio, Magdalena; Kephart, Josiah L.; Williams, Kendra N.; Shade, Timothy; Adekunle, Temi; Steenland, Kyle; Naeher, Luke P.; Moulton, Lawrence H.; Gonzales, Gustavo F.; Chiang, Marilu; Hossen, Shakir; Chartier, Ryan T.; et al. (Environmental health perspectives, 2022)
Household air pollution (HAP) from biomass fuel combustion remains a leading environmental risk factor for morbidity worldwide. Measure the effect of liquefied petroleum gas (LPG) interventions on HAP exposures in Puno, Peru. We conducted a 1-y randomized controlled trial followed by a 1-y pragmatic crossover trial in 180 women age 25-64 y. During the first year, intervention participants received a free LPG stove, continuous fuel delivery, and regular behavioral messaging, whereas controls continued their biomass cooking practices. During the second year, control participants received a free LPG stove, regular behavioral messaging, and vouchers to obtain LPG tanks from a nearby distributor, whereas fuel distribution stopped for intervention participants. We collected 48-h kitchen area concentrations and personal exposures to fine particulate matter (PM) with aerodynamic diameter ( ), black carbon (BC), and carbon monoxide (CO) at baseline and 3-, 6-, 12-, 18-, and 24-months post randomization. Baseline (kitchen area concentrations vs. ; personal exposure vs. ), CO (kitchen vs. ; personal vs. ), and BC (kitchen vs. ; personal vs. ) were similar between control and intervention participants. Intervention participants had consistently lower concentrations at the 12-month visit for kitchen ( , , and ) and personal exposures ( , , and ) to , BC, and CO when compared to controls during the first year. In the second year, we observed comparable HAP reductions among controls after the voucher-based intervention for LPG fuel was implemented (24-month visit , BC, and CO kitchen mean concentrations of , , and and personal exposures of , , and , respectively), and average reductions were present among intervention participants even after free fuel distribution stopped (24-month visit , BC, and CO kitchen mean concentrations of , , and and personal exposures of , , and , respectively). Both home delivery and voucher-based provision of free LPG over a 1-y period, in combination with provision of a free LPG stove and longitudinal behavioral messaging, reduced HAP to levels below 24-h World Health Organization air quality guidelines. Moreover, the effects of the intervention on HAP persisted for a year after fuel delivery stopped. Such strategies could be applied in LPG programs to reduce HAP and potentially improve health. https://doi.org/10.1289/EHP10054.